Islamized and Lumad Populations and other Identifiable Indigenous Inhabitants in Mindanao, Sulu and Palawan Based on Mother Tongue by Municipality, 1990 Census - R. Rodil, B. (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)